Heloros, Italien: Hellenistische Heiligtümer in Sizilien - Wolf, Markus (e-Forschungsberichte des DAI, 2023)
Thanks to the new extensive structural recording and study of the sanctuary of Demeter in the Syracusan sub-colony of Heloros it was possible to better grasp the situation in Hellenistic Eastern Sicily and Hiero’s architecture and building program and to shed new light through the peculiar models on the building and cultural activities by Hiero II. Through the study of the Heloros complex, which represents a key point for the understanding of the Hellenistic architecture in Sicily in the 3rd century BC, it was possible to complete the historical overview of Hellenistic sanctuaries in Sicily.